2-Chloro-5-nitroaniline - Saeed, Aamer (International Union of Crystallography, 2009)
The molecule of the title compound, C(6)H(5)ClN(2)O(2), is close to being planar (rms deviation = 0.032 Å for all non-H atoms), with a maximum deviation of −0.107 (3) Å for an O atom. In the crystal structure, intermolecular N—H⋯O and N—H⋯N interactions link the molecules into a three-dimensional network.